NON-INVASIVE FAULT DIAGNOSIS OF GEARBOX CRACK IN ELECTROMECHANICAL DRIVE SYSTEM BASED ON STATOR CURRENT SIGNAL ANALYSIS OF THREE-PHASE AC ASYNCHRONOUS MOTOR - BAI GuoZhen; WANG Lu; LI BingChu; WANG ShuangYuan (Jixie qiangdu)
Gear crack failure is a high incidence of the electromechanical transmission system, and timely detection of the crack failure is of great significance to ensure the normal operation of the electromechanical transmission system. Proposes a non-invasive diagnosis method for gear crack faults based on the stator current signal of a three-phase AC asynchronous motor. First, establish a motor-gear-load electromechanical coupling model, and use the potential energy method to calculate the variable meshing stiffness of the gear under different crack lengths and angles; Then, the electromechanical coupling model is numerically solved by Runge-Kutta method to analyze the dynamic response of motor current under the influence of time-varying meshing stiffness. In response, by comparing the stator current spectra of healthy gears and cracked faulted gears, the current spectrum characteristics corresponding to the gear crack faults are revealed, and the drive system gear crack fault diagnosis criterion based on the analysis of the motor current signal is established. The motor driving experiment is carried out on the gear with crack fault, and the motor current signal under the influence of the gear crack fault is consistent with the numerical solution result. The proposed non-invasive diagnosis method of gear crack fault based on motor current signal is of high value for reducing the maintenance cost of transmission system.